Rhetoric, Precarity, and mHealth Technologies. Issue 3 (26th May 2016) - Teston, Christa
Abstract : Wearable technologies in general and mHealth data in particular are championed frequently for ways they afford individual agency and empowerment and promote what the Robert Wood Johnson Foundation (RWJF) calls a "culture of health." This article complicates such epideictic rhetorics based on results from a situational analysis of the RWJF's Data for Health listening events, which incorporated panelists from the RWJF, JawBone, Inc., the Quantified Self, and other mHealth technology organizations as well as audience participants who work in community health. Given panelists' and audiences' diverging claims about how mHealth data either succeed or fail in creating a culture of health, I mobilize precarity as an analytic construct for critiquing the coexistence of technoscientific progress alongside the persistence of health disparities among vulnerable populations.